PENGARUHINVESTASITERHADAP PRODUK DOMESTIK BRUTO DI INDONESIA (Sebelum dan Sesudah Otonomi Daerah) - Prabowo, Muhadi; Rahman, M. Taufiqur (JURNAL INFO ARTHA, 2015)
Economic growth is associated with the gain of national income reflected by the presence of gross domestic product increase. Thus, in this case, every country certainly always assumes the economic growth as a measuring rod of developmental success for the country. In the presence of the increasingly gross domestic product, in addition to describe on the better economic rate situation of some country, it also reflects the population welfare level. For this reason, the objective of this research was to evaluate the effect of variables of foreign investment and domestic investment simultaneously or collectively and partially or individually on the Indonesian gross domestic product before and after regional autonomy. This research use multiple linear regression method with natural logarithm, F test, t-test analysis.Results of this research showed that the threeof independent variables tested collectively had an effectdependent variables in amount of 92.8% and the rest of 7.2% was explained by other variables which werenot tested in this research. From the t-test showed that variable of domestic investment and regional autonomy had a significant effect on variable of gross domestic product.While variable of foreign investment had no significant effect on variable of grossdomestic product.